The acceptance of standardization language in society - Sari Siregar , Nurmaliana; Rakasiwi, Rani; Inayah Hutasuhut, Nurul (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
This research is aimed to identify the acceptance of standardization language in the society. Acceptance is one of the processes in standardizing the language. In this research, the researcher is curious whether standardization of language can be accepted in society. This research was conducted in qualitative descriptive. Qualitative descriptive aimed to explore and clarify one phenomenon or social reality by describing some variables related to the problem identified order to fulfill this research, the researcher took around 20 people as the sample to prove that they accepted the standardization language. The researcher also took the data from KBBI as the lead in order to know the standard language. Having done the research, it can be drawn that there were many people who did not know the standardization language. It means that even though the language has been standardized unfortunately it could not be accepted by the citizen. And the finding shows that the standardizing language of mercon, menteri and telur are more popular with which around 11 people got the correct answers or 55 % meanwhile non-standardizing language of etempramen, nimbun, and telekung are not familiar to them. There are 15 persons got the incorrect answers or around 75 %.